Attention bias to negative versus non-negative faces is related to negative affectivity in a transdiagnostic youth sample. (June 2021) - Harrewijn, Anita; Abend, Rany; Naim, Reut; Haller, Simone P.; Stavish, Caitlin M.; Bajaj, Mira A.; Matsumoto, Chika; Dombek, Kelly; Cardinale, Elise M.; Kircanski, Katharina; Brotman, Melissa A.
Abstract: This study identified a shared pathophysiological mechanism of pediatric anxiety and irritability. Clinically, anxiety and irritability are common, co-occurring problems, both characterized by high-arousal negative affective states. Behaviorally, anxiety and irritability are associated with aberrant threat processing. To build on these findings, we examined eye-tracking measures of attention bias in relation to the unique and shared features of anxiety and irritability in a transdiagnostic sample of youth ( n  = 97, 58% female, M age  = 13.03, SD age  = 2.82). We measured attention bias to negative versus non-negative emotional faces during a passive viewing task. We employed bifactor analysis to parse the unique and shared variance of anxiety and irritability symptoms from self- and parent-report questionnaires. Negative affectivity is the derived latent factor reflecting shared variance of anxiety and irritability. We found that higher negative affectivity was associated with looking longer at negative versus non-negative faces, reflecting a shared mechanism of anxiety and irritability. This finding suggests that modification of elevated attention to negative emotional faces may represent a common potential treatment target of anxiety and irritability. Highlights: We studied attention bias as unique or shared mechanisms of anxiety and irritability. We measured attention bias using eye-tracking in a transdiagnostic youth sample. Negative affectivity is a bifactor-derived common factor of anxiety and irritability. Negative affectivity was related to looking longer at negative vs non-negative faces. This finding might reflect a shared mechanism of anxiety and irritability.